Pan-hysterectomy for Closed Pyometra in a Dog - Mathew, Dayamon David; Kumar, Vinod; Udehiya, Rahul Kumar; Singh, Naresh Kumar (Biology, Engineering, Medicine and Science Reports)
Pyometra is infection of the uterus with presence of pus inside the uterus. A 2.5 years old intact female dog weighing 25 kgs was presented with a history of anorexia and pain on palpation of thoraco-abdominal region. On physical examination, the abdomen was tensed. Lateral abdominal radiography and ultrasonography was performed and diagnosed as pyometra which is a closed-cervix type. Pan-hysterectomy was performed under general anesthesia as treatment to save the animal. Post-operatively the animal was on antibiotics and anti-inflammatory drugs for 5 days and kept on fluid therapy for 3 days. The pet had an uneventful recovery.
Keywords: Hysterectomy; Pan-hysterectomy; Closed pyometra; Open pyometra; Dog